The Use of High-Intensity Focused Ultrasound (HIFU) Plus 150mg Bicalutamide as First Line Salvage Therapy for Local Recurrent Prostate Cancer - Cao, Jian-zhou; Su, Rui; Pan, Jin-feng; Yan, Ze-jun; Ma, Qi (Frontiers in Oncology, 2021)
Patients with localized prostate cancer (PCa) are often treated with radical prostatectomy (RP). However, more than 30% of such patients have high risk of recurrence. Salvage radiotherapy (SRT), androgen deprivation therapy (ADT) and combination of radiotherapy and ADT are the standard care for recurrent PCa. Recently, high intensity focused ultrasound (HIFU) has gradually applied in the treatment of recurrent PCa. Here, we proposed a hypothesis that combined HIFU and bicalutamide 150mg as first line salvage therapy to treat patients with local recurrent PCa with visible lesions due to the following advantages: (1) HIFU is effective in reducing local tumor load, and bicalutamide 150mg is a feasible and safety option to combine with HIFU. (2) Compared with radiotherapy, HIFU plus 150mg bicalutamide is minimal invasiveness with fewer adverse effects and better quality of life(QOL); (3) Radiotherapy can be preserved as the second-line salvage method in the cases who are failure to HIFU and 150mg bicalutamide combination. More clinical trials are warranted to confirm this hypothesis in treatment with recurrent PCa.